2019
DOI: 10.1002/jcp.28678
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐derived exosomal lncRNA GAS5 as a biomarker for early‐stage non‐small‐cell lung cancer diagnosis

Abstract: Diagnosis and treatment at an early stage may improve survival of non-small-cell lung cancer (NSCLC). Previous studies have found that long noncoding RNA growth arrestspecific transcript 5 (GAS5) is essential to cancer progression. However, the expression and diagnostic value of GAS5 in exosomes (Exo-GAS5) remain unclear. One hundred and four participants were enrolled, including subjects with NSCLC (n = 64) and healthy subjects (n = 40). The total Exosome Isolation Kit was applied to isolate exosomes from ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(96 citation statements)
references
References 39 publications
1
95
0
Order By: Relevance
“…For example, a research has provided a proof that the exosomes derived from endothelial progenitor cells can promote the regeneration and differentiation of osteoclast precursors through lncRNA MALAT1, thereby promoting bone repair [27]. It has been showed that expression of the lncRNA GAS5 in secreted exosomes is elevated and exosomes can dynamically monitor the level of GAS5 [28]. Another article has suggested that lncRNA ATB may exert an enormous function on the regulation of the microenvironment of glioma by exosomes [29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a research has provided a proof that the exosomes derived from endothelial progenitor cells can promote the regeneration and differentiation of osteoclast precursors through lncRNA MALAT1, thereby promoting bone repair [27]. It has been showed that expression of the lncRNA GAS5 in secreted exosomes is elevated and exosomes can dynamically monitor the level of GAS5 [28]. Another article has suggested that lncRNA ATB may exert an enormous function on the regulation of the microenvironment of glioma by exosomes [29].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al demonstrated that the expression of noncoding RNA growth arrest-specific transcript 5 (GAS5) in circulating exosomes (Exo-GAS5) could be an ideal non-invasive blood-based tumor marker for the identification of patients with early-stage NSCLC. The expression of Exo-GAS5 was significantly lower in NSCLC patients than in healthy controls (p < 0.001) and higher in early-stage compared with advanced-stage NSCLC patients (p = 0.045) [82]. Recently, Zhang et al demonstrated that the expression of exosomal miR-17-5p was significantly higher in NSCLC patients than in healthy controls (p < 0.001).…”
Section: Exosomesmentioning
confidence: 98%
“…In serum from non-small cell lung cancer (NSCLC) patients, exosomal MALAT-1 (metastasis associated lung adenocarcinoma transcript 1) was higher compared to healthy patients [79] . In contract, serum exosomal GAS5 was down-regulated in NSCLC patients and negatively correlated with tumor stages [80] . Other research group, reported that exosomes containing SOX2-OT (Sox2 overlapping transcript) are enriched in plasma from patients with lung squamous cell carcinoma [81] .…”
Section: Roles Of Exosomal Lncrnasmentioning
confidence: 88%